Unravelling corrosion degradation of aged aircraft components protected by chromate-based coatings - Cornet, A.J.; Homborg, A.M.; Anusuyadevi, P.R.; Hoen - Velterop, L. 't; Mol, J.M.C. (Elsevier, 2024)
Despite extensive research, eliminating hexavalent chromium-based inhibitors from aerospace coatings remains challenging due to a lack of understanding of coating degradation during aircraft service. This study addresses the issue by investigating the protective mechanisms and aging processes of chromate-containing coatings on aircraft components after service for over 35 years. Four aircraft parts underwent visual inspection, disassembly, and analysis using scanning electron microscopy (SEM) and X-ray Photoelectron Spectroscopy (XPS). While most coating areas remained intact after extended use, three distinct degradation modes were identified: tip erosion, corrosion around rivets, and corrosion around fasteners at the leading edge. These findings reveal the complexity of corrosion protection, emphasizing that hexavalent chromium-containing coatings may not offer comprehensive protection at local design heterogeneities. The study also highlights the need to revisit traditional laboratory analysis protocols based on accelerated corrosion testing of oversimplified sample configurations, given the revealed end-of-service failure mechanisms.